Editor's Choice – Trends in Lower Extremity Amputation Incidence in European Union 15+ Countries 1990–2017. (October 2020) - Hughes, Will; Goodall, Richard; Salciccioli, Justin D.; Marshall, Dominic C.; Davies, Alun H.; Shalhoub, Joseph
Abstract : Objective: Lower extremity amputation (LEA) carries significant mortality, morbidity, and health economic burden. In the Western world, it most commonly results from complications of peripheral arterial occlusive disease (PAOD) or diabetic foot disease. The incidence of PAOD has declined in Europe, the United States, and parts of Australasia. The present study aimed to assess trends in LEA incidence in European Union (EU15+) countries for the years 1990–2017. Methods: This was an observational study using data obtained from the 2017 Global Burden of Disease (GBD) Study. Age standardised incidence rates (ASIRs) for LEA (stratified into toe amputation, and LEA proximal to toes) were extracted from the GBD Results Tool (http://ghdx.healthdata.org/gbd-results-tool ) for EU15+ countries for each of the years 1990–2017. Trends were analysed using Joinpoint regression analysis. Results: Between 1990 and 2017, variable trends in the incidence of LEA were observed in EU15+ countries. For LEAs proximal to toes, increasing trends were observed in six of 19 countries and decreasing trends in nine of 19 countries, with four countries showing varying trends between sexes. For toe amputation, increasing trends were observed in eight of 19 countries and decreasing trends in eight of 19 countries for both sexes, with three countries showing varying trends between sexes. Australia had the highest ASIRs for both sexes in all LEAs at all time points, with steadily increasing trends. The USA observed the greatest reduction in all LEAs in both sexes over the time period analysed (LEAs proximal to toes: female patients −22.93%, male patients −29.76%; toe amputation: female patients −29.93%, male patients −32.67%). The greatest overall increase in incidence was observed in Australia. Conclusion: Variable trends in LEA incidence were observed across EU15+ countries. These trends do not reflect previously observed reductions in incidence of PAOD over the same time period.